Eugenics and special education in the Czech lands during the Interwar Period: The beginning of segregation against disabled and Roma - Victoria Schmidt (Social Work and Society, 2016)
This text puts forwards the argument that the development of education for deviant and disabled children and the formation of practices aimed at controlling the Roma population during socialism echo those developed during the interwar period. The introduction engages with the current trend to revise social welfare policies and practices in the light of the history of eugenics. Then, the text turns to the case of Czech lands where the institutionalization of Roma surveillance was outstandingly pervasive in comparison to the rest of Central and Eastern Europe. The first part explores the development of eugenics in the Czech lands and establishes a temporal framework needed for the understanding of the relationship between eugenics and child protection. The second part discusses how eugenic ideas were applied within correctional institutions for minors with delinquent behavior and mental disability. In the third part I examine the reform towards forced legitimization of the nomad Roma , payingspecial attention to the institutionalization of Roma children. In the final part, I discuss the historical implications for s the path dependencyand segregation of the Roma population in the Czech lands.